COMIC MEDIA IN BIOLOGY EDUCATION BASED ON SOCIO-SCIENTIFIC ISSUES AND IT'S EFFECTIVITY: A NARRATIVE LITERATURE STUDY - Daniswara, Karinda Rahma; Fadilah, Muhyiatul (BIOCHEPHY: Journal of Science Education, 2025)
In the learning and teaching process, students need tools that can make them easily visualize the learning they get. Coupled with the socio-scientific issues contained in the comic storyline, comics can easily enter the scope of students' reading. With the help of technology and information, educational media in the form of comics are made to increase students' awareness to live healthier, lives by staying away from things that are bad for their health. The purpose of making this article is to determine the effect of using comic media as a biology educational media, to make it easier for students to visualize biology material with the help of interesting stories and pictures based on socio-scientific issues. To collect the data, we analyze 12 article compatible with the issue by using narrative literature study method. The results of these literature study article, students are much more understanding of the concept of material and visualization of material through comic media.